Development of Online Inquiry Learning Model Based on Ethnomathematics Javanese Culture for Middle School Students - Pardimin, P; Setiana, Dafid Slamet; Supriadi, Didi (Universitas Sarjanawiyata Tamansiswa, 2022)
The success of character education during the Covid 19 pandemic experienced many obstacles, considering that learning at school was carried out online. However, through the online system, the massive development of information technology may erode the noble cultural character of students. Efforts to create students with characteristics that match the personality of the Indonesian nation during the Covid 19 pandemic are not enough through the implementation of learning based on the curriculum that has been implemented. These efforts can be made through ethnomathematics, namely integrating cultural elements into learning mathematics. Inquiry learning is done through investigation and discovery to develop conceptual understanding. This study aims to develop an online inquiry mathematics learning model based on Javanese cultural ethnomathematics. The research method to be carried out is Research and Development, which refers to the educational development model from Plomp. The construction phase begins with coordination activities with the school where the research trials are carried out. Then a small-scale trial was carried out by carrying out online learning using the learning model that had been developed. Small-scale trials were conducted in four schools. Furthermore, the implementation of large-scale trials in eight schools. The twelve schools were taken from junior high schools in the Provinces of DIY, Central Java, and East Java. The test, evaluation, and revision stages continue the previous stage. The model is validated by a judgment expert, namely an expert in mathematics learning models, to test whether the developed model can be understood and accepted by users. The study's results showed that the user's assessment of the Javanese ethnomathematics-based inquiry learning model showed excellent results. Users state that they understand the learning model developed, including the learning model's syntax, social systems, learning principles, learning support systems, instructional impacts, and accompanying impacts. The user ratings of the learning module show high scores in the introductory, content, evaluation, and closing aspects. Users also stated good results for student worksheets, including aspects of the completeness of student worksheet components, content, materials, language, and learning model requirements.